Reﬂections on the impact of mental health in patients with a diagnosis of arterial hypertension with a look at the use of mobile devices in telehealth - Palacio Vásquez, Marta Lucia
This article aims to develop a strategy that strengthens the quality of life of patients through healthy physical and mental habits, emphasizing mainly mental health, since according to the world health organization it is "a state of well-being in which the individual is aware of their own capabilities, can cope with the normal stresses of life, can work productively and fruitfully and is able to make a contribution to their community”. It is very important to keep the above in mind because populations with cardiovascular risk, especially arterial hypertension: HT. Sometimes they do not know the relationship that this concept has with their pathological, sociological and psychological state, that is why it is key through the health services both in person and remotely to educate patients with cardiovascular conditions about the incidence that their mental health may have in the signs of the pathology; it is vitally important to give guidelines of healthy mental lifestyles so that patients understand, understand and do not question behaviors that can occur both on a personal and social level derived from bad mental habits in the cardiovascular pathology, mainly in hypertension.